2008
DOI: 10.1016/j.ejvs.2007.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Meta Analysis on Mortality of Ruptured Abdominal Aortic Aneurysms

Abstract: This meta-analysis suggests that mortality of patients with RAAA treated by open surgery has not changed over the past 15 years. This could be explained by increased age of patients undergoing RAAA repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
1
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(83 citation statements)
references
References 102 publications
3
70
1
9
Order By: Relevance
“…Yapılan çalışmalarda son iki dekadda ameliyat sırası bakımda sağlanan ilerlemelere karşın rüptüre AAA'ya ilişkin acil cerrahi girişimin mortalite oranının %45-50 arasında değiştiği bildirilmiştir. [14][15][16][17] Son yıllarda AAA'nın tedavisinde endovasküler aortik anevrizma tamiri (EVAR) artmıştır. Dahası Bulut ve Demirağ [18] yaptıkları çalışmada, uygun anatomili ve açık cerrahi ile yüksek ameliyat sırası mortalite ve morbidite beklenen hastalarda EVAR'ın doğru bir tedavi yöntemi olduğu ve EVAR veya açık cerrahi ile tedavi edilenlerin kısa ve orta dönem yaşam kaliteleri karşılaştırıldığında, EVAR'la tedavi edilenlerin yaşam kalitelerinin daha iyi olduğunun izlendiği bildirilmiştir.…”
Section: Discussionunclassified
“…Yapılan çalışmalarda son iki dekadda ameliyat sırası bakımda sağlanan ilerlemelere karşın rüptüre AAA'ya ilişkin acil cerrahi girişimin mortalite oranının %45-50 arasında değiştiği bildirilmiştir. [14][15][16][17] Son yıllarda AAA'nın tedavisinde endovasküler aortik anevrizma tamiri (EVAR) artmıştır. Dahası Bulut ve Demirağ [18] yaptıkları çalışmada, uygun anatomili ve açık cerrahi ile yüksek ameliyat sırası mortalite ve morbidite beklenen hastalarda EVAR'ın doğru bir tedavi yöntemi olduğu ve EVAR veya açık cerrahi ile tedavi edilenlerin kısa ve orta dönem yaşam kaliteleri karşılaştırıldığında, EVAR'la tedavi edilenlerin yaşam kalitelerinin daha iyi olduğunun izlendiği bildirilmiştir.…”
Section: Discussionunclassified
“…Despite many recent advances in surgical and anesthetic peri-operative management, the operative mortality after open repair of ruptured AAA has remained fairly constant. A meta-analysis by Hoornweg and colleagues 15) in 2008 which included over 100 studies and approximately 60000 patients with ruptured aneurysms showed an overall mortality rate of 48.5% for open repair. This high mortality rate is probably related to factors such as delay in recognition and intervention, extreme hemodynamic instability, profound blood loss and suboptimal peri-operative care in the emergency setting.…”
Section: Discussionmentioning
confidence: 99%
“…All three units function at the NHSL, which is the largest tertiary care hospital in the country situated in the capital Colombo, with a bed-strength of over 4000. There is approximately equal distribution of cases among the units with an annual case volume of [15][16][17][18][19][20] each. This is a government sponsored national health care system with free health care for all.…”
Section: Introductionmentioning
confidence: 99%
“…7) However, results showing that the overall ruptured AAA mortality was much lower in a surgical unit − which offered the patients both open repair and EVAR − than that which is generally accepted suggest that emergency EVAR can be an effective option in the treatment of ruptured AAA, when operators select patients that will benefit from EVAR over open surgery. [8][9][10] In our case, we chose to treat the ruptured AAA by emergency EVAR because there were experienced operators for EVAR in our hospital and because the EVAR components were immediately available at that time. Furthermore, the patient had severe comorbidities and also had an aneurysm that was anatomically suitable for EVAR.…”
Section: Discussionmentioning
confidence: 99%